2001
DOI: 10.1046/j.1365-2672.2001.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of brown tyrosine pigments by the yeast Yarrowia lipolytica

Abstract: Aims: To study the mechanism of production of brown pigments from tyrosine in the yeast Yarrowia lipolytica. Methods and Results: Pigment formation was followed during growth in tyrosine medium, and the presence of the pigment precursor in the medium was assessed by evaluating pigment formation after removing the cells at different times of incubation. It was observed that the pigment precursor accumulated outside the cells during the exponential phase of growth, but pigment formation only occurred during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
0
40
1
Order By: Relevance
“…Since the chemical structure of melanins is still unknown and pyomelanin formation is presently proved by detecting the formation of HGA from tyrosine (8,18,36), it seems likely that the pigments of Y. lipolytica are pyomelanins. Furthermore, we have previously demonstrated that these pigments are polymers in which the main monomer is derived from tyrosine and has a general chemical structure compatible with the structure of HGA (6). To the best of our knowledge, the involvement of HGA in the production of brown pigments has not been reported for fungi.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Since the chemical structure of melanins is still unknown and pyomelanin formation is presently proved by detecting the formation of HGA from tyrosine (8,18,36), it seems likely that the pigments of Y. lipolytica are pyomelanins. Furthermore, we have previously demonstrated that these pigments are polymers in which the main monomer is derived from tyrosine and has a general chemical structure compatible with the structure of HGA (6). To the best of our knowledge, the involvement of HGA in the production of brown pigments has not been reported for fungi.…”
Section: Discussionmentioning
confidence: 97%
“…The involvement of Y. lipolytica in the browning defects of cheese seems to result from its ability to produce brown pigments from tyrosine (6,27). The technological conditions under which browning develops are not yet established, and it remains unclear why this phenomenon has a sporadic occurrence even in cheeses where this species is usually present.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations